Mitigating planetary catastrophes with a call for ecological wisdom through contemporary American poems - Yulianto, Henrikus Joko (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2023)
In today’s digital technology era, humans orientate toward material fulfillment. This manner often neglects his care about nonhuman organisms and the natural environment in general. The impacts are that nowadays temperature is getting higher and biodiversity is dwindling or disappearing due to the rising temperature and deforested lands. Global warming is the ongoing climatic phenomenon that is now prevalent on earth today along with the surging digitalization in daily social and cultural life. Humans need to retreat and think it over in order to prevent the condition from deteriorating and from further catastrophes. Poetry as one literary genre might be one outlet for humans to think about what it means to be humans in this one and only earth household. Contemporary American poems are the epitome of raising present issues about anthropocentrism and its impacts on the degradation of the physical environment. This brief paper discusses some American contemporary poems of Denise Levertov, Susan Stewart, and Robinson Jeffers. Levertov’s poem “Brother Ivy”; Stewart’s long poem “The Rose”; and Jeffers’s poem, “Life from the Lifeless” are the epitome of poetic works that aim to humanize and anthropomorphize nonhuman things and organisms such as forest, rock, and plant. These are the actions humans should do to preserve the biotic life from demolition because of various anthropogenic activities. Reading and understanding ecological views in these poems as a poetic discourse helps ones to ecologize their thoughts and action to sustain the planetary robustness.